2020
DOI: 10.3847/1538-4357/ab8065
|View full text |Cite
|
Sign up to set email alerts
|

Disk Structure around the Class I Protostar L1489 IRS Revealed by ALMA: A Warped-disk System

Abstract: We have observed the Class I protostar L1489 IRS with the Atacama Millimeter/submillimeter Array (ALMA) in Band 6. The C 18 O J =2-1 line emission shows flattened and non-axisymmetric structures in the same direction as its velocity gradient due to rotation. We discovered that the C 18 O emission shows dips at a radius of ∼200-300 au while the 1.3 mm continuum emission extends smoothly up to r ∼ 400 au. At the radius of the C 18 O dips, the rotational axis of the outer portion appears to be tilted by ∼15 • fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(79 citation statements)
references
References 92 publications
(144 reference statements)
20
59
0
Order By: Relevance
“…The current resolution does not resolve the inner 10au; hence, the reduction in CO emission is more extended. In IRAS04302, a similar offset of Sai et al (2020). The slight rise seen in C 18 O emission around ∼300 au to the southwest of the continuum peak is also visible in the C 17 O radial cut.…”
Section: O and H 2 Co Morphologymentioning
confidence: 60%
“…The current resolution does not resolve the inner 10au; hence, the reduction in CO emission is more extended. In IRAS04302, a similar offset of Sai et al (2020). The slight rise seen in C 18 O emission around ∼300 au to the southwest of the continuum peak is also visible in the C 17 O radial cut.…”
Section: O and H 2 Co Morphologymentioning
confidence: 60%
“…Thus, dust evolution is unlikely a dominant mechanism in determining the disk size distribution observed in the millimeter continuum. In addition, in a few embedded Class 0 and I protostars, where the disk radii were measured with gas kinematics, the disk radii observed in the millimeter continuum are comparable to the dynamically measured disk radii within a factor of two (e.g., Ohashi et al 2014;Yen et al 2014;Aso et al 2015Aso et al , 2017Sai et al 2020). For a given protostar, the separation is defined as its distance to the protostar nearest to it.…”
Section: Potential Biases Due To Multiplicity and Evolutionmentioning
confidence: 54%
“…The dynamical mass of L1489 IRS was also estimated to be ∼1.6 M (Yen et al 2014;Sai et al 2020), which is relatively larger than other protostars whose dynamical masses were es-timated (Murillo et al 2013;Harsono et al 2014;Chou et al 2014;Lee et al 2014;Aso et al 2015Aso et al , 2017. The systemic velocity of L1489 IRS was estimated from the Keplerian rotation to be 7.22 km s −1 (Sai et al 2020). We have adopted v LSR = 7.22 km s −1 for the systemic velocity of L1489 IRS in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Yen et al (2014) have identified a Keplerian disk with a radius of ∼700 au, which is the largest one identified around a Class I protostar so far, and two infalling flows accreting onto the disk surface based on their ALMA 12-m array observations in the C 18 O 2-1 emission at angular resolutions of ∼ 1 . Sai et al (2020) have reexamined the gas kinematics at an angular resolution about three times higher than that in Yen et al (2014), revealing that a Keplerian disk with a radius of ∼600 au is surrounded by an infalling envelope with a constant specific angular momentum. The dynamical mass of L1489 IRS was also estimated to be ∼1.6 M (Yen et al 2014;Sai et al 2020), which is relatively larger than other protostars whose dynamical masses were es-timated (Murillo et al 2013;Harsono et al 2014;Chou et al 2014;Lee et al 2014;Aso et al 2015Aso et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation